Impactos da pandemia de Covid-19 no Sistema de Transporte Público por Ônibus em São João da Boa Vista - SP - Gontijo, Geisa Aparecida da Silva; Pereira Junior, Weslei Augusto; Sales, Pedro Henrique da Silva (ANAP Brazil, 2021)
.